Creeping Attachment Involving Dental Implants: Two Case Reports with a Two-Year Follow-Up from an Ongoing Clinical Study - Armando R. Lopes Pereira Neto; Bernardo Born Passoni; José Moisés de Souza; João Gustavo Oliveira de Souza; César Augusto Magalhães Benfatti; Ricardo de Souza Magini; Marco Aurélio Bianchini (Hindawi Limited, 2014)
Introduction. This paper describes case reports where coronal growth of soft tissue on implant threads was observed after surgery for soft tissue graft. This phenomenon is known as "creeping attachment." Methods. Two patients were submitted to gingival graft procedure including subepithelial connective tissue graft and masticatory mucosal graft. A two-year follow-up appointment was performed. Results. After a two-year follow-up gingival growth over titanium surfaces characterizing the "creeping attachment" phenomenon was observed. This gingival growth happened over abutment and threads surfaces. Conclusion. The creeping attachment phenomenon is possible over titanium surfaces and has not yet been reported in the relevant literature over this kind of structure.